Franki Raffles, photographe engagée : la photographie féministe en Écosse dans les années 1980 et 1990 - Marine Benoit-Blain (Les Cahiers de l'École du Louvre)
Kept in the Special Collections Division of the University of St Andrews, the collection of the images and archives of the photographer Franki Raffles (1955–1994) is the fruit of a short but prolific career, marked by political activism. Raffles devoted her life to the deconstruction of the power relations inherent in the dynamics of representation, particularly in documentary photography. Her photographic oeuvre was thus exclusively dedicated to the representation of women as independent figures. Heavily influenced by far-left schools of thought, particularly Marxist-Leninist philosophy, she subverted a univocal tradition of representation to make photography a tool for dialogue and communication. A passionate, complex and politically committed figure, Raffles became the ambassador for the practice of photography as a tool for struggle and protest, and her work was militant and feminist.